Strengthening the Role and Function of the Honorary Court of the Indonesian People's Representative Council in Enforcing the Code of Ethics - Moh. Taufik; Muh. Harley Maulana (FKIP, Universitas Palangka Raya, 2024)
The aim of this research is to find out the role and function of the Court of the People's Representative Council of the Republic of Indonesia in dealing with violations of the council's code of ethics. This research approach was carried out using a normative approach. From this research it can be seen that the role of the Council's Honorary Court in upholding the DPR's code of ethics is carried out through prevention and enforcement efforts. Prevention efforts are carried out in various stages, namely socialization, training, sending circulars and providing recommendations, or other methods determined by the Honorary Court Council.